Recent progress on biological control of Fusarium wilt in vegetable crops - Feng Xiong; Mingfeng Guo; Yawen Liu; Xiaochen Liu; Jiahui Fu; JunZhu Gao; Man Yang; Rui Ma; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Crop Protection, 2026)

Tailoring microstructure of coal-based hard carbon and electrochemical performance for sodium-ion battery anodes: Insights from the intrinsic properties of diverse coal precursors - Weibo Meng; Hui Guo; Baolin Xing; Qiaomiao Xu; Man Wang; Long Li; Huihui Zeng; Xiaoxiao Qu; Chuanxiang Zhang; Peng Li; Yijun Cao (Fuel, 2026)

Multi-scale structure and rheological properties of curdlan/gelatin composite gels: Correlating molecular interactions with gelation mechanisms - Wangxin Qu; Man Li; Xu Zhang; Guoyan Yang; Zhili Ji; Wangyang Shen (Food Hydrocolloids, 2026)

DAF-16/FOXO insulin signaling modulates F-53B toxicity by regulating intestinal redox homeostasis and permeability in Caenorhabditis elegans - Qinlin Wu; He Chen; Man Qu (Chemico-Biological Interactions, 2026)

Ultrafast degradation of carbamazepine by Fe(II)-EDDS co-activated persulfate: Non-radical species play a major role - Jiangfei Qin; Shenbao Qu; Man Wei; Xia Hu; Aijiang Yang; Yunman Wa; Jiahui Huang; Changbiao Tai (Journal of Water Process Engineering, 2026)

Regional mapping of soil heavy metals via a novel deep learning approach: A case study in the Yangtze River Delta, China - Lei Ju; Bifeng Hu; Mingkai Qu; Jun Man (Journal of Hazardous Materials, 2026)

Boron and manganese co-doped magnetic biochar for soil lead stabilization: Influencing factors, performance, and mechanisms - Jinyao Zhang; Xu Liu; Yunqi Shi; Hongyang Man; Yujie Ze; Yunxi Liu; Yue Tao; Jianhua Qu; Ying Zhang (Process Safety and Environmental Protection, 2026)

Ascorbic acid enhances the activation of peroxymonosulfate by Schwertmannite/biochar composites for emerging organic contaminants degradation - Shenbao Qu; Hongyan Yang; Ruyi Wang; Man Wei; Xia Hu; Aijiang Yang; Shiying Song (Desalination, 2026)

MIP-YOLO11: An Underwater Object Detection Model Based on Improved YOLO11 - Xinyu Qu; Ying Shao; Zheng Wang; Man Chang (Journal of Marine Science and Engineering, 2026)
Due to challenges such as inadequate lighting, water scattering, high density of small objects, and complex object morphology in underwater environments, traditional YOLO11 models face difficulties including interference from complex backgrounds, weak perception of small objects, and insufficient feature extraction when applied underwater. This paper proposes an improved MIP-YOLO11 model for underwater object detection based on the YOLO11 framework. First, a MCEA module is designed in the backbone network to replace the basic CBS convolution module. Through a lightweight multi-branch convolutional structure, the perception ability for small objects, object edges, contours, and morphological features in underwater scenes are enhanced without significantly increasing computational overhead. Second, an IMCA module based on the coordinate attention mechanism is introduced at the end of the backbone network to replace the C2PSA module, reducing the number of model parameters while maintaining detection accuracy. Finally, the Bottleneck module in C3k2 is improved by incorporating a PConv and a dual residual connection mechanism, thereby expanding the receptive field and enhancing the efficiency of complex feature extraction. Experimental results demonstrate that MIP-YOLO11 significantly outperforms the traditional YOLO11 in underwater environments. P and R are improved by 2.5% and 4.1%, respectively. Moreover, the mAP0.5 and mAP0.5:0.95 metrics are increased by 4.2% and 7.5%, respectively. The improved model achieves a good balance between high accuracy and light weight, and can provide a more reliable underwater object detection scheme for AUV underwater detection and other application scenarios.

The novel PFOS substitute OBS induces visual developmental toxicity in zebrafish embryos via ferroptosis - Xing Liu; Xinyi Wu; Mingzhu Xia; Yi Fan; Yichun Zhao; Junjie Han; Ruobing Chen; Yuting Peng; Man Qu (Toxicology Letters, 2026)

Cadophorin C, a new cyclic heptapeptide isolated from a mangrove-derived fungus Penicillium sp. GXIMD 03101 - Jia-Li He; Xiao-Dong Jiang; Yu-Man Gan; Xin-Jian Qu; Xiang-Xi Yi; Yong-Hong Liu; Cheng-Hai Gao; Meng Bai (Natural Product Research, 2026)

Glycine Drives IMP Production in Hybrid Bream (Megalobrama Amblycephala ♀ × Culter Alburnus ♂) Via Concerted Action: Activating glycyl-tRNA Synthetase and Fueling the Pentose Phosphate Pathway - Zhehua Xu; Weiting Zhang; Ruijie Zhan; Jiefan Zhou; Man Chen; Yonghua Zhou; Fufa Qu; Rong Zhou; Shaochun Liu; Shenping Cao; Jianzhou Tang; Zhen Liu (Marine Biotechnology, 2026)

Nomilin ameliorates perfluorooctanoic acid (PFOA)-induced impairment of zebrafish (Danio rerio) ocular development and visual function through PIK3CA activation - Xing Liu; Mingzhu Xia; Xinyi Wu; Ruobing Chen; Yuting Peng; Yi Fan; Junjie Han; Yichun Zhao; Man Qu (Toxicology and Applied Pharmacology, 2026)

Corrigendum to “Composite inclusion complexes containing hyaluronic acid/chitosan nanosystems for dual responsive enrofloxacin release” [Carbohydrate Polymers 252 (2021) 117162] - Yuda Liu; Dongmei Chen; Aoxue Zhang; Man Xiao; Zhenxia Li; Wanhe Luo; Yuanhu Pan; Wei Qu; Shuyu Xie (Carbohydrate Polymers, 2026)

Nomilin mitigates OBS-induced developmental cardiotoxicity via the Nrf2 pathway - Xing Liu; Yi Fan; Ruobing Chen; Yuting Peng; Xinyi Wu; Mingzhu Xia; Yichun Zhao; Junjie Han; Man Qu (Aquatic Toxicology, 2026)

High-performance edible alginate straws constructed with zein coatings by phase separation and electrostatic assembly after gradient diffusion - Yunpeng Qu; Yuanpu Liu; Kexin Shi; Jiabo Wang; Yanfei Wang; Meng Ma; Qingjie Sun; Fengwei Xie; Man Li (Food Packaging and Shelf Life, 2025)

Biomimetic hydrogel microsphere encapsulated superoxide dismutase enzymes alleviate postoperative peritoneal adhesion by modulating oxidative stress-inflammation cycles via Piezo1 mechanosensitive channels - Shuting Yang; Chao Qu; Xuetao Yuan; Ke Liu; Kai Deng; Jiayin Du; Yuanbo Wang; Man Xu; Li Zhang; Mingzhen Zhang; Ting Liang; Xuqi Li (Chemical Engineering Journal, 2025)

The modified biochar of Acidithiobacillus ferrooxidans effectively promotes the peroxonosulfate degradation of ibuprofen in the presence of light: Singlet oxygen constitutes the principal active oxygen species - Man Wei; Shenbao Qu; Ruyi Wang; Xia Hu; Jiti Zhou; Aijiang Yang; Shiying Song (Journal of Environmental Chemical Engineering, 2025)

Programming BioZ, a promiscuous enzyme in bacterial biotin synthesis - Yongchang Xu; Shuyu Zhou; Tao Cui; Jiuxin Qu; Huimin Zhang; Man Huang; Youjun Feng (Science Bulletin, 2025)

Synergistic effects of PGPR and organic fertilizer on soil fertility, enzyme activities, and microbial community composition in saline-alkali rice systems - Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Jiahui Fu; Rui Ma; Feng Xiong; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Applied Soil Ecology, 2025)

Dynamic changes of rice sheath non-structural carbohydrates and source-sink balance under elevated atmospheric CO2 concentration and temperature stresses - Hao He; Jiabin Shi; Mingjie Chen; Jing Zhao; Kexi Qu; Man Li; Lin Zhao; Yuanyuan Wang; Zhenghua Hu; Qi Li (Journal of Plant Physiology, 2025)

Comprehensive wheat lodging detection under different UAV heights using machine/deep learning models - Jianing Long; Zhao Zhang; Qu Zhang; Xiaohui Zhao; C. Igathinathane; Jianfei Xing; Chayan Kumer Saha; Wenyi Sheng; Han Li; Man Zhang (Computers and Electronics in Agriculture, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Advanced oxidation processes mediated by Schwertmannite for the degradation of organic emerging contaminants: Mechanism and synergistic approach - Shenbao Qu; Ruyi Wang; Man Wei; Xia Hu; Xingyi Song (Journal of Water Process Engineering, 2024)

Selective phthalate removal by molecularly imprinted biomass carbon modified electro-Fenton cathode - Mengyao Liu; Shenbao Qu; Hongdi Mou; Man Wei; Xia Hu; Aijiang Yang (Bioresource Technology, 2024)

New insights into the remediation of chromium-contaminated industrial electroplating wastewater by an innovative nano-modified biochar derived from spent mushroom substrate: Mechanisms, batch study, stability and application - Jingyi Wang; Yongduo Guan; Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Xuesheng Liu; Wei Wang; Yu Jin; Juanjuan Qu (Chemosphere, 2024)

Efficient chromium remediation using eco-innovative biochar in a novel two-stage upflow fixed bed system - Jingyi Wang; Yongduo Guan; Jiahui Fu; Xiaochen Liu; Mingfeng Guo; Junzhu Gao; Man Yang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Journal of Water Process Engineering, 2024)

Screening of saline-alkali tolerant microorganisms and their promoting effects on rice growth under saline-alkali stress - Jiahui Fu; Yawen Liu; Xiaochen Liu; Mingfeng Guo; Junzhu Gao; Man Yang; Xuesheng Liu; Wei Wang; Yu Jin; Juanjuan Qu (Journal of Cleaner Production, 2024)

MnO2 and sonosensitizer-based nano-platforms for cancer sonodynamic therapy - Jinfeng Yang; Yunqi Man; Danyang Qu; Yue Cao; Hui Shi; Xinyi Guo; Zhenbao Liu; Meilin Shi (Chemical Engineering Journal, 2024)

Research advances in detection of food adulteration and application of MALDI-TOF MS: A review - Danliangmin Song; Kai Dong; Shiyu Liu; Shiqian Fu; Feng Zhao; Chaoxin Man; Yujun Jiang; Kuangyu Zhao; Bo Qu; Xinyan Yang (Food Chemistry, 2024)

Improvement of heterogeneous electro-Fenton oxidation of dimethyl phthalate by embedding Fe/Co bimetallic active sites into waste wine lees biochar - Shenbao Qu; Wenpei Guo; HongDi Mou; Ruyi Wang; Man Wei; Xia Hu (Journal of Water Process Engineering, 2024)

Corrigendum to ‘Personal exposure monitoring of fine and coarse particulate matter using exposure assessment models for elderly residents in Hong Kong’ [Chemosphere 357 (June 2024) 141975] - Ka Hei Lui; Tianhang Zhang; Chung Ling Man; Chi Shing Chan; Steven Sai Hang Ho; Linli Qu; Helen Hoi Ling Kwok; Timothy Chi Yui Kwok; Kin Fai Ho (Chemosphere, 2024)

Impact of climate change on the potential allocation of resources of rice cultivation in Yangtze-Huai Rivers region: a case study of Anhui Province, China - Hao He; Mingjie Chen; Man Li; Kexi Qu; Huihui Dang; Qi Li; Zhenghua Hu; Qing Zhang (Theoretical and Applied Climatology, 2024)

Chronic Fluoride Exposure Induces Ovarian Dysfunction and Potential Association with Premature Ovarian Failure in Female Rats - Xiaoke Tang; Hongjuan Li; Yali Wang; Li Zeng; Ling Long; Yajun Qu; Hui Yang; Xiaolin Zhang; Yanmin Li; Yanni Yu; Qi Zhou; Man Luo (Biological Trace Element Research, 2024)

Elevated CO2 results in modified N2O emissions from paddy rice fields - Hao He; Zhurong Wu; Yuanyuan Wang; Chao Liu; Mingjie Chen; Kexi Qu; Man Li; Jing Zhao; Zhenghua Hu; Qi Li (Nutrient Cycling in Agroecosystems, 2024)

Personal exposure monitoring of fine and coarse particulate matter using exposure assessment models for elderly residents in Hong Kong - Ka Hei Lui; Tianhang Zhang; Chung Ling Man; Chi Shing Chan; Steven Sai Hang Ho; Linli Qu; Helen Hoi Ling Kwok; Timothy Chi Yui Kwok; Kin Fai Ho (Chemosphere, 2024)

LncRNA KCNQ1OT1/miR-496/HMGB1 Signaling Axis Promotes Invasion and Migration of Non-small Cell Lung Cancer Cells - Yan Wang; Xiao-yun Jiang; Man-ying Qu; Jie Liang; Jia-sheng Yang; Rui-lin Sun (Biochemical Genetics, 2024)

Exploration of natural processes and anthropogenic inputs by Zn isotopes in suspended particulate matter: A case study from the Lancang River in Southwest China - Yang Tang; Guilin Han; Rui Qu; Jinke Liu; Man Liu (Environmental Pollution, 2024)

Characteristics and sources of oxygenated VOCs in Hong Kong: Implications for ozone formation - Fanglin Wang; Steven Sai Hang Ho; Chung Ling Man; Linli Qu; Zhe Wang; Zhi Ning; Kin Fai Ho (Science of The Total Environment, 2024)

Iron isotope fractionation of redox and geochemical cycling in the typical Gleysols in Mun River Basin, Northeast Thailand - Qian Zhang; Guilin Han; Jie Zeng; Lingqing Wang; Guangyou Zhu; Man Liu; Bin Liang; Rui Qu; Xiaoqiang Li; Shitong Zhang (Science of The Total Environment, 2023)

Contribution of the bacterial community of poorly fermented oat silage to biogas emissions on the Qinghai Tibetan Plateau - Chaosheng Liao; Binbin Na; Xiaolong Tang; Man Zhao; Changbing Zhang; Shiyong Chen; Minghong You; Binqiang Bai; Lizhuang Hao; Dorjeeh Tondrob; Guangpeng Qu; Shuqing Yang; et al. (Science of The Total Environment, 2023)

Microwave-assisted one-pot preparation of magnetic cactus-derived hydrochar for efficient removal of lead(Ⅱ) and phenol from water: Performance and mechanism exploration - Jianhua Qu; Zhaolin Du; Yue Lei; Man Li; Wei Peng; Mengning Wang; Jie Liu; Qi Hu; Lei Wang; Yifan Wang; Ying Zhang (Bioresource Technology, 2023)

Exposure to epoxy-modified nanoplastics in the range of μg/L causes dysregulated intestinal permeability, reproductive capacity, and mitochondrial homeostasis by affecting antioxidant system in Caenorhabditis elegans - Man Qu; Yuhan An; Xinyi Jiang; Qinlin Wu; Long Miao; Xing Zhang; Yang Wang (Aquatic Toxicology, 2023)

Using association mapping and local interval haplotype association analysis to improve the cotton drought stress response - Wenju Gao; Qin Chen; Jincheng Fu; Hui Jiang; Fenglei Sun; Shiwei Geng; Yuxiang Wang; Jieyin Zhao; Yuting Xie; Man Zhou; Yanying Qu; Quanjia Chen (Plant Science, 2023)

LDHA and LDHB overexpression promoted the Warburg effect in malignantly transformed GES-1 cells induced by N-nitroso compounds - Xing Liu; Xihuan Zou; Yueyue Zhou; Ruobing Chen; Yuting Peng; Man Qu (Food and Chemical Toxicology, 2023)

SKN-1/Nrf2-dependent regulation of mitochondrial homeostasis modulates transgenerational toxicity induced by nanoplastics with different surface charges in Caenorhabditis elegans - Man Qu; Long Miao; He Chen; Xing Zhang; Yang Wang (Journal of Hazardous Materials, 2023)

Extracellular polymeric substances and mineral interfacial reactions control the simultaneous immobilization and reduction of arsenic (As(V)) - Jinzhao Chen; Chenchen Qu; Man Lu; Ming Zhang; Yichao Wu; Chunhui Gao; Qiaoyun Huang; Peng Cai (Journal of Hazardous Materials, 2023)

Fe contents and isotopes in suspended particulate matter of Lancang River in Southwest China - Yang Tang; Guilin Han; Liu Man; Jie Zeng; Rui Qu (Science of The Total Environment, 2023)

Integrative transcriptome and metabolome revealed the molecular mechanism of Bacillus megaterium BT22-mediated growth promotion in Arabidopsis thaliana - Xiao Liu; Yan Du; Xiaofan Na; Man Wang; Ying Qu; Linghui Ge; Yuanmeng Wang; Linqi Gao; Wenke Bai; Yurong Bi; Libin Zhou (Journal of Plant Physiology, 2023)

Acute exposure to polystyrene nanoplastics inhibits the flocculation of activated sludge - Jianwei Qu; Hanxiang Li; Shanshan Xu; Jie Huang; Zhiping Liu; Man Long; Jinsong Guo; Fang Fang (Journal of Environmental Chemical Engineering, 2023)

Geochemical processes and indicative significance of rare earth elements in high arsenic geothermal fluids in Batang, western Sichuan, China - wei Zhang; hanxiong Zhang; guiling Wang; jiayi Zhao; gaofan Yue; man Li; shuaichao Wei; zewei Qu (Geothermics, 2023)

Development of human dermal PBPK models for the bisphenols BPA, BPS, BPF, and BPAF with parallel-layered skin compartment: Basing on dermal administration studies in humans - Man Hu; Zhichun Zhang; Yining Zhang; Ming Zhan; Weidong Qu; Gengsheng He; Ying Zhou (Science of The Total Environment, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Asymmetric intramolecular charge transfer enables highly efficient red thermally activated delayed fluorescent emitters - Chao Qu; Huiqin Wang; Yi Man; Zhe Li; Peng Ma; Peng Chang; Xin Li; Chunmiao Han; Yudong Pang; Hui Xu (Chemical Engineering Journal, 2023)

Dolominol a and B, two new neolignans from Dolomiaea souliei (Franch.) C.Shih - Man Yi; Fan-Cheng Meng; Shen-Yue Qu; Jing-Xin Mao; Guowei Wang; Mingxing Liu; Zhi-Hua Liao; Min Chen (Natural Product Research, 2022)

Cerebral vasculitis caused by Talaromyces marneffei and Aspergillus niger in a HIV-positive patient: a case report and literature review - Yidong Gao; Man Qu; Chao Song; Lufeng Yin; Min Zhang (Journal of NeuroVirology, 2022)
Cerebral vasculitis is a long-standing but flourishing and fadeless research topic. Infections are a frequent cause of cerebral vasculitis, vital to diagnose due to involvement of specific anti-infection treatments. A 65-year-old man visited the hospital for his neurological symptoms without obvious inducements. After admission, radiological examination and comprehensive conventional microbiological tests (CMTs) revealed suspected intracranial infectious vasculitis. Metagenomic next-generation sequencing (mNGS) and reverse transcription-polymerase chain reaction further confirmed that his cerebral vasculitis was caused by Talaromyces marneffei ( T. marneffei ) and Aspergillus niger ( A. niger ) co-infection. The patient’s final diagnosis changed from initial herpetic encephalitis, due to the past history of cephalosome and facial herpes and non-significant antiviral therapeutic effects, to fungal cerebral vasculitis. The patient was discharged after use of targeted antifungal therapies on day 18 of his admission, and his associated symptoms disappeared completely at follow-up 3 weeks later. We first illustrated the presence of uncommon cerebral vasculitis caused by T. marneffei and A. niger in a human immunodeficiency virus-positive patient. In clinically suspected patients with infectious cerebral vasculitis, mNGS should be performed to detect potential pathogens if CMTs may not provide useful pathogenic clues, highlighting the importance of mNGS in the diagnosis and treatment of infectious diseases.

Rubus chingii var. suavissimus alleviates high-fat diet-induced lipid metabolism disorder via modulation of the PPARs/SREBP pathway in Syrian golden hamsters - Man-Jing Jiang; Li Li; Wan-Fang Huang; Jian Su; Yao-Hua Li; Xiao-Sheng Qu; Lan-Lan Fan (Journal of Natural Medicines, 2021)

Identification and mapping of CpPM10.1, a major gene involved in powdery mildew (race 2 France of Podosphaera xanthii) resistance in zucchini (Cucurbita pepo L.) - Yunli Wang; Cong Qi; Yusong Luo; Feng Zhang; Zuyun Dai; Man Li; Shuping Qu (Theoretical and Applied Genetics, 2021)

Fetal growth, fetal development, and placental features in women with polycystic ovary syndrome: analysis based on fetal and placental magnetic resonance imaging - Qing Zhang; Zhong-kun Bao; Mei-xiang Deng; Qiong Xu; Dan-dan Ding; Man-man Pan; Xi Xi; Fang-fang Wang; Yu Zou; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2020)

Transcriptional profiling analysis of OsDT11-mediated ABA-dependent signal pathway for drought tolerance in rice - Man Zhao; Yanhu Ju; Bo Zhao; Xiaoming Li; LIli Dai; Jicheng Qu; Zhaohui Chu; Xinhua Ding (Plant Biotechnology Reports, 2020)

A new neolignan glycoside from Dolomiaea souliei - Man Yi; Fan-Cheng Meng; Shen-Yue Qu; Yun-Yi Tao; Zhi-Hua- Liao; Min Chen (Natural Product Research, 2020)

Diversity Distributions and the Anthocyanin Associations of Fungal Endophytes in Different Colored Grapevine Leaves - Jing-Chao Chen; Man Yu; Fang Liu; Jin-Zhuo Qu; Xiao-Xia Pan; Han-Bo Zhang; Ming-Zhi Yang (Journal of Plant Biology, 2020)

Characterization of Cucurbita maxima Fruit Metabolomic Profiling and Transcriptome to Reveal Fruit Quality and Ripening Gene Expression Patterns - He-Xun Huang; Ting Yu; Jun-Xing Li; Shu-Ping Qu; Man-Man Wang; Ting-Quan Wu; Yu-Juan Zhong (Journal of Plant Biology, 2019)

Optimization of Hydrolysis Conditions for the Isolation of Angiotensin-I Converting Enzyme (ACE) Inhibitory Peptides from Rhopilema hispidum - Zhenliang Sun; Huanlong Qin; Duo Cao; Xuebing Yan; Hao Li; Linsheng Huang; Xiao Qu; Cheng Kong; Man Wang (Journal of Ocean University of China, 2018)